REHABILITASI LAHAN TERDEGRADASI PASCA PENAMBANGAN TIMAH DI DABO, PULAU SINGKEP: PERTUMBUHAN DAN PENAMPILAN PADI GOGO - Robinson Harahap; MH Siagian (Research Center for Biology-Indonesian Institute of Sciences, 2004)
Exploitation of natural resources often brings unexpected effects on the enviroment. This is happened in well-known Indonesian mining area of tin i.e. in Singkep Island, Riau Province.The accumulation of tailing as a mining waste, degraded the soil quality both chemical and physical aspects.To restore the degraded (death) land post-mining, biological agents must be introduced, to restore the biological processes within the soil as close as possible to their original conditions pre-mining.Planting rice in post mining land is thought to be one of the step to biologically, restore the quality of post-mining soil. A study of the seven upland rice varieties was conducted at Dabo village, Singkep District, Riau, using Randomized Block Design (RBD), within the scheme of introducing biological agent to post-mining soil.The high varities of upland rice consisted Jatiluhur, Limboto, Maninjau, Ranau,TB154 E.TB-2, Way Rarem and as comparison was local Pacitan variety.The results indicated that the plant heigh appereance of the high varities of upland rice variety was better compared to the local Pacitan variety, but the amount of seedling per bush of the local Pacitan variety was more at 45 and 60 days after planting. The average of panicle length on the high varities of upland rice 2 was 73.34 cm which was longer then the comparing local Pacitan variety. Biomass weight and grains production per m on the high 2 varities of upland rice was heavier than comparing local Pacitan variety. The high production of grain per m were 520 and 510 grams on the TB154 E.TB-2 and Limboto varieties respectively.Among the high variety of upland rice there were high diversities 2on plant height, total seedling per bush, panicle length, biomass weight and grain production per m .There were assumed to be influenced by habitat and genetic factors.The high varities of upland rice were able to grow and produce well on the nutrient poor soil and at low soil pH (4.87).